2016
DOI: 10.1186/s13068-016-0591-1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the co-metabolism of glycerol and glucose in Escherichia coli by genetic engineering, transcription profiling, and 13C metabolic flux analysis

Abstract: BackgroundGlycerol, a byproduct of biodiesel, has become a readily available and inexpensive carbon source for the production of high-value products. However, the main drawback of glycerol utilization is the low consumption rate and shortage of NADPH formation, which may limit the production of NADPH-requiring products. To overcome these problems, we constructed a carbon catabolite repression-negative ΔptsGglpK* mutant by both blocking a key glucose PTS transporter and enhancing the glycerol conversion. The mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 69 publications
7
19
1
Order By: Relevance
“…5 c, d). In reality, inhibition of EMPP flux (e.g., removal of glucose transporter Δ ptsG or glucose-limiting chemostat cultures) allows E. coli to cometabolize glycerol with glucose [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 c, d). In reality, inhibition of EMPP flux (e.g., removal of glucose transporter Δ ptsG or glucose-limiting chemostat cultures) allows E. coli to cometabolize glycerol with glucose [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strain SA‐B4 had the highest shikimate production in the culture medium with a 12:1 glycerol to glucose ratio portraying that changing the ratio of glycerol to glucose can influence the shikimic acid production. NADPH is an essential cofactor in the biosynthesis of shikimic acid . In this study, we demonstrated that NADPH availability had a positive correlation with shikimate production.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon sources might influence the kinetics of desired product through a cellular response that redistributes the composition of the fermentation end‐products to maintain an oxidation–reduction (redox) equilibrium. The metabolic profiles resulting from varying carbon sources have been explicated by metabolic stoichiometric analysis and revealed the existence of different regulatory networks . Optimizing the carbon source is important to achieve elevated shikimate production with effective substrate conversion accompanied by diminished by‐product generation.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore co-expressed glycerol kinase (glpK) and sn-glycerol-3phosphate dehydrogenase (glpD) genes using the pPROLar.A122 vector backbone, since it was compatible with the plasmid used to express L-asparaginase in the DKO strain. Many previous studies have shown that these two genes play a critical role in enhancing glycerol uptake rates [20,[55][56][57][58].…”
Section: Growth and Substrate Utilization Pro Les Of The Dko Strain Pmentioning
confidence: 99%